Public citizens : the attack on big government and the remaking of American liberalism - Sabin, Paul, 1970- (W.W. Norton & Company, 2021)
"The story of the dramatic postwar struggle over the proper role of citizens and government in American society. In the 1960s and 70s, an insurgent attack on traditional liberalism took shape in America, built on new ideals of citizen advocacy and the public interest. Environmentalists, social critics, and consumer advocates like Rachel Carson, Jane Jacobs, Ralph Nader, and others crusaded against what they saw as a misguided and often corrupt government. Drawing energy from civil rights protests and opposition to the Vietnam War, the new citizens movement drew legions of followers and scored major victories, disrupting plans for highways and dams, banning harmful chemicals, and blocking pipelines. In the process, citizen advocates helped to undermine big government liberalism and, ironically, clear the way for Reagan-era "free market" conservatives who sought to slash regulations and enrich corporations. Public Citizens traces the history of the public interest movement and explores its tangled legacy, showing the ways New Deal liberalism fell apart and the challenges in trying to replace it"--